The Influence Of Islamic Perspective Leadership And Work Motivation On Employee Performance - Epndi, Ependi (International Journal of Social and Management Studies, 2021)
This study aims to determine the influence of Islamic perspective leadership and work motivation either partially or simultaneously on employee performance. The method used in this research is to collect data by distributing questionnaires to employees of PT. Wings Abadi Airlines. The sample in this study were 30 respondents. Sampling using the Judgment Sampling method, namely the sample is taken according to the desired character, whoever the respondent is concerned, wherever and whenever it is found. The instrument in this study has passed the validity and reliability test stages. Test for normality, heteroscedasticity and multicollinearity. Analysis of the data using multiple regression analysis, correlation, and determinant analysis as well as hypothesis testing. The results of the study partially Islamic perspective leadership affects performance and partially work motivation affects performance and simultaneously Islamic perspective leadership and work motivation together affect employee performance